DETECTION OF SUPERHUMPS IN THE DWARF NOVA PV PERSEI - Vanmunster, T. (Одеські астрономічні публікації, 2017)
The CBA (Center for Backyard Astrophysics) Belgium Observatory belongs to a global network of small photometric telescopes, that study periodic phenomena in Cataclysmic Variables (CVs). This network is among the leading examples of successful partnerships between professional and amateur astronomers. In a few occasions. CBA stations operate on a stand-alone basis on some selected CVs. This paper reports the results of such an individual photometry campaign. The dwarf nova PV Per was observed for three nights during its outburst in September 1996 at the CBA Belgium Observatory. Unfiltered differential CCD photometry revealed superhumps with a period of 0.oSO5:I:0.00ol days. This finding establishes PV Per as being a new member of the SU UMa-type dwarf novae.